Two new species of the genus Diestramima from China (Orthoptera: Rhaphidophoridae: Aemodogryllinae) - He, Zhu-Qing; Yu, Zhe-Yuan; Zong, Jing-Song; Di, Mi; Shen, Zi-Hao; Liu, Yi-Jiao; Qin, Yan-Yan; Li, Kai (Zootaxa, 2023)
The genus Diestramima comprises 41 species from Asia with 31 species distributed in China. In this study, we reconstruct the phylogeny tree of Diestramima species by maximum likelihood and Bayesian inference based on three mitochondrial genes (COI, 12S and 16S). The result indicates that the phylogenetic results are coherent with that based on five molecular markers (COI, 12S, 16S, 18S and 28S). Moreover, two new species, D. pingmengensis sp. nov. He & Zong and D. gulinjingensis. sp. nov. Zong & He are described. Their validities are also supported by morphological features. Furthermore, D. sichuanensis Zhu & Shi, 2022 is treated as a junior synonym of D. guangxiensis Qin, Wang, Liu & Li, 2016 based on both morphological and molecular features.